Surplus to extraction: Resettlement as a "make live" intervention in Mozambique. (March 2022) - Wiegink, Nikkie; Kronenburg García, Angela
Highlights: Extractive projects create surplus populations. Resettlement is a make-live intervention in intention. Resettlement processes are often experienced as let-die scenarios. Being made surplus produces claims of dependency. A diverse (and fuzzy) resettlement governance landscape allows for the deflection of responsibility for surplus populations. Abstract: One of the direct consequences of the growing extractive industry in Mozambique is the displacement of people from their homes and lands. Building on the work of Tania Li (2010), we regard extractive projects as one of the key ways in which "surplus populations" are produced in Mozambique, as people lose access to their lands without being substantially incorporated into the job markets that extractive projects create. In this paper, we critically explore Li's framework of "make live" interventions and "let die" scenarios for conceptualising the consequences of being made surplus to extraction. We focus on involuntary resettlement processes in Mozambique as make live interventions (in intention). While Li describes make live interventions in terms of a choice made by governing actors, we see resettlement as a messy and conflict-ridden process that is often experienced as a let die scenario. We also reveal the heterogeneity of governing actors (primarily state and company) involved in make live interventions and the claims of dependency of populations affected by resettlement that such interventions produce. We draw from research material gathered during different resettlement processes and phases in extractive contexts in Cabo Delgado and Tete provinces in Mozambique.